A DFT study of DMC formation on Rh‐doped Cu/AC surfaces. Issue 13 (20th April 2015) - Ren, Jun; Yang, Jinzhou; Wang, Wei; Guo, Hailong; Zuo, Zhijun; Lin, Jianying; Li, Zhong
<x xml:space="preserve">Abstract</x> The activity and selectivity of heterogeneous catalysts can be significantly improved by dispersion of another active component in the metal substrate. The impact of Rh promoter on the formation of dimethyl carbonate (DMC) via oxidative carbonylation of methanol on Cu–Rh/AC (activated carbon) catalyst was investigated by density functional theory calculations. The most stable configurations of reacting species (CO, OH, CH3O, monomethyl carbonate, and DMC) adsorbed on the Cu0(zero‐valent copper)/AC and Cu–Rh/AC surfaces were determined on the basis of the calculated results. The reaction energy and activation energy of the rate‐limiting steps on the Cu–Rh/AC and Cu0/AC surfaces were compared. The activation energies of the rate‐limiting step of CO insertion into dimethoxide are 206.3 and 304.8 kJ mol−1 on the Cu–Rh/AC and Cu0/AC surfaces, respectively. The activation energies of the rate‐limiting step of CO insertion into methoxide are 78.5 and 92.7 kJ/mol on the Cu–Rh/AC and Cu0/AC surfaces, respectively. The calculated results indicate that the addition of Rh atom has a significant effect on decreasing the active energy the main pathway for DMC formation. © 2015 Wiley Periodicals, Inc.